The impaired response of circulating asprosin concentrations to glucose levels fluctuation may be one of the causes of type 2 diabetes - a narrative review - Paulina Trojanowska; Alina Trojanowska; Joanna Szydełko; Ewa Tywanek; Robert Jan Łuczyk (Kazimierz Wielki University, 2020)
It has been recently discovered that asprosin, an adopakine that is secreted by white adipose tissue, affects the release of glucose into the blood. When blood glucose levels rise, the production of asprosin is immediately suppressed. In healthy people, circulating asprosin shows daily fluctuations, and its concentration drops significantly with the beginning of eating. In patients with type 2 diabetes it was invastigated that both fasting and postprandial asprosin concentrations were significantly higher. Therefore, it is probable that elevated blood levels of asprosin and its impaired response to glucose levels fluctuation may be one of the causes of type 2 diabetes. It is considered, that administration of antibodies that block the action of asprosin may help diabetics reduce glucose levels. In addition, it can also contribute to the effective fight against obesity.